Analysis of satisfaction in the use of technological simulation tools in the learning of the Automatic Process Control course - León Velarde, César Gerardo (2021)
The objective of this article is to describe the satisfaction of students with the use of technological simulation tools in learning in the automatic process control course, as part of the pedagogical update in the context of dis-tance education. The Academic Satisfaction Scale (ESA) was used as a meas-urement instrument, the reliability of the data was performed through Cronbach's alpha, giving a consistencyvalue of 0.949. When developing the re-search, it was determined that 56.8% of the students are satisfied with the aca-demic experience of their learning using technological simulation tools in the virtual environment. On the other hand, 11.4% of students indicated that the content transmitted in this course does not excite them and they do not feel comfortable, these results will allow generating feedback to the teacher in their pedagogical techniques and teaching methods. Likewise, by means of R squared, it can be indicated that satisfaction towards the use of technological simulation tools in the course of automatic process control influences 63.7% in the evaluation of general satisfaction with the academic experience in the Vir-tual environment.